2020
DOI: 10.3762/bjnano.11.128
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-level integration of self-aligned high aspect ratio silicon 3D structures using the MACE method with Au, Pd, Pt, Cu, and Ir

Abstract: The wafer-level integration of high aspect ratio silicon nanostructures is an essential part of the fabrication of nanodevices. Metal-assisted chemical etching (MACE) is a promising low-cost and high-volume technique for the generation of vertically aligned silicon nanowires. Noble metal nanoparticles were used to locally etch the silicon substrate. This work demonstrates a bottom-up self-assembly approach for noble metal nanoparticle formation and the subsequent silicon wet etching. The macroscopic wafer patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…83−89 Figure 5 shows the scheme of SiNWs synthesis by MACE with a silver metal salt. 90 The morphology of SiNWs could be altered by tuning several etching parameters such as nature of the metal catalyst, etching time, etching temperature, concentration of oxidation (H 2 O 2 ), etching (HF) agents, and intrinsic properties of silicon (e.g., orientation, doping type, doping level). 91,92,46 In a pioneering work, the review by Toor et al 93 correlation of etching parameters on the resultant SiNWs.…”
Section: Metal Nanoparticles Decorated Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…83−89 Figure 5 shows the scheme of SiNWs synthesis by MACE with a silver metal salt. 90 The morphology of SiNWs could be altered by tuning several etching parameters such as nature of the metal catalyst, etching time, etching temperature, concentration of oxidation (H 2 O 2 ), etching (HF) agents, and intrinsic properties of silicon (e.g., orientation, doping type, doping level). 91,92,46 In a pioneering work, the review by Toor et al 93 correlation of etching parameters on the resultant SiNWs.…”
Section: Metal Nanoparticles Decorated Siliconmentioning
confidence: 99%
“…Recently, a review by Leonardi et al has extensively discussed all the conventional techniques and investigated their possibilities in the commercial transfer of technology in microelectronics and optoelectronics in a single chip by counting the stability, cost, reproducibility, and complexity in the synthesis . The MACE mechanism involves a charge transfer process between a metal catalyst and silicon, which necessitates the oxidation and dissolution of Si. Figure shows the scheme of SiNWs synthesis by MACE with a silver metal salt . The morphology of SiNWs could be altered by tuning several etching parameters such as nature of the metal catalyst, etching time, etching temperature, concentration of oxidation (H 2 O 2 ), etching (HF) agents, and intrinsic properties of silicon (e.g., orientation, doping type, doping level). ,, In a pioneering work, the review by Toor et al demonstrated a direct correlation of etching parameters on the resultant SiNWs.…”
Section: Metal Nanoparticles Decorated Silicon Nanowiresmentioning
confidence: 99%
“…Some etching mechanisms have been proposed to explain the MACE process. A reduction reaction for the cathodic process implies the decomposition of H 2 O 2 at the metallic surface in acidic conditions [46][47][48][49][50].…”
Section: Reactions Of the Mace Anisotropic Wet Etching Process For Si...mentioning
confidence: 99%
“…In this process, the silicon is oxidized to SiO 2 and SiF 2− 6 . The holes h + generated are consumed by the silicon substrate and the anodic process occurring under the metallic deposited silver could be described as follows [46,47,50,52]:…”
Section: Reactions Of the Mace Anisotropic Wet Etching Process For Si...mentioning
confidence: 99%
See 1 more Smart Citation